Teaching Teachers to Offer STEM to Undergrads. - Guzdial, Mark (Communications of the ACM, 2020)
The author discusses the importance of training K-12 teachers in computer science (CS) education in order to permit colleges and universities to offer CS, computer programming, and STEM education courses to undergraduate students.